Between comparison and commensuration: a case-study of COVID-19 rankings. Issue 2 (June 2021) - Nelken, David
Abstract: Global social indicators, as a form of governance and soft regulation, exert pressure for change and compliance through the way they compare and rank the relative performance of states or other units. Is it reasonable then to expect the comparisons they make in the process of carrying out such strategic exercises to be accurate and fair? In particular, how far can they, or should they, be required to be faithful to the requirement to 'compare like with like'. Using as an example the role of indicators in documenting and responding to the current coronavirus epidemic, I investigate the way their hybrid combination of both comparison and commensuration may help to account for the difficulty they have had so far in establishing stable rankings of best practice.